Oxford new syllabus primary Mathematics workbook 1A for grade 1 - Yee, Dr foong pui (Karachi : Oxford university press, 2019)
The Oxford New Syllabus Primary Mathematics Workbook 1A is designed to provide students with additional practice and reinforcement of mathematical concepts introduced in the corresponding textbook. This workbook is aimed at primary school students, usually in their first year, and aligns with the curriculum to support learning through exercises and activities.
Keywords: Mathematics : Textbook